Toâ€™-otoâ€™- The Local Wisdom of Madurese Ethnic Families and Perceptions - Devika, Ferdiya; Prajawati, Maretha Ika; S, Basir (Merdeka Malang University, 2020)
The to'-otoâ€™ a tradition is an event held by the community to return bhubuwan's money (money given at weddings). Each implemented certainly has different perceptions of toâ€™-otoâ€™ that have been entrenched. This is the main problem that researchers want to know. This research uses a qualitative research method with a phenomenal research model to look deeper into the psychological meaning of an individualâ€™s experience of the toâ€™-otoâ€™ tradition. The results showed that the tradition of toâ€™-otoâ€™ was perceived as a means of returning savings due to the necessities of life, a means of tightening the silaturrahim rope of both the head of the family in the village or outside the village, one form of â€œtasyakuranâ€ (salvation) and as a form of tradition that the community runs.DOI:Â https://doi.org/10.26905/lw.v12i2.4149